2023
DOI: 10.4103/sjg.sjg_163_23
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and colorectal cancer in Eastern Mediterranean Regional Office (EMRO): A systematic review and meta-analysis

Mohammad-Hossein Keivanlou,
Ehsan Amini-Salehi,
Soheil Hassanipour
et al.

Abstract: Background: Smoking poses a significant risk for colorectal cancer (CRC), considered the third leading reason for cancer-related deaths worldwide. However, there has been limited research on the relationship between smoking and CRC in the Eastern Mediterranean Regional Office (EMRO). Therefore, a meta-analysis was conducted to combine available data and gain a comprehensive understanding of the relationship between smoking and CRC in EMRO. Methods: Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Environmental factors and dietary habits in this region may also contribute to an elevated risk of CRC in this region. According to a meta-analysis, smoking emerged as a significant risk factor for CRC in the EMRO region 60 . Seyyedsalehi et al, through a multicenter case–control study in Iran, identified a significant positive association between CRC and high dietary total fat intake 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors and dietary habits in this region may also contribute to an elevated risk of CRC in this region. According to a meta-analysis, smoking emerged as a significant risk factor for CRC in the EMRO region 60 . Seyyedsalehi et al, through a multicenter case–control study in Iran, identified a significant positive association between CRC and high dietary total fat intake 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the epidemiological models, environmental factors can affect individuals based on a person's genetic characteristics, including age, gender, personality, and physical state, causing IBD susceptibility [10,12]. Eastern Mediterranean Regional Office (EMRO) includes 22 countries which is one of the World Health Organization regional classifications [13]. The epidemiology of IBD was studies in the EMRO countries separately but a comprehensive study to assess IBD epidemiology was lacking hence we performed a comprehensive metaanalysis study to investigated epidemiological status of IBD in this region.…”
Section: Introductionmentioning
confidence: 99%